Model characteristics of water polo players' activities in vertical position - Bratusa, Z. F.; Matkovic, I. Z.; Dopsaj, M. (2002)
During a match, a water polo player spends approximately 63% of the total time in vertical position (1). This indicates that vertical position, with the structure of technical-tactical activities derived from it, is the most dominant in comparison with other activities. The task of this research was to define model activities realized during a match by a player in vertical position.